THE PERSPECTIVE OF TRANSPORT ROUTES IN TÜRKIYE BASED ON THE SWOT MODEL - Tishehyar, M.; Shirkhani, Sh. (Journal of Oriental Studies, 2024)
Türkiye, the strategic bridge between Asia and Europe, has a unique geopolitical position that encourages cooperation with neighboring and regional partners. The purpose of this study is to identify the key transport corridors in Türkiye using the SWOT model and evaluate the potential of these routes. The purpose of this research is to discover the current transportation and communication capacities of Türkiye and how they are useful for neighboring countries and Central Asia. This study examines strengths, weaknesses, opportunities, and threats to address challenges and uncover opportunities.Issues such as lack of budget, imbalance in energy transfer and political instability of neighboring countries have affected the country and make it face challenges. But the ports of Türkiye and the favorable geopolitical position of Türkiye, as well as the presence of extensive airline lines and important airlines company such as Turkish Airline, in this country, is a significant potential for commercial and economic growth in the transportation sector. If the challenges are resolved and attention is paid to the opportunities and privileged positions of Türkiye and the countries of Central Asia, they will be able to benefit from cooperation. Key words: Türkiye, Transportation Corridors, Energy, SWOT model, Central Asian Countries.